Exploring Teachers' Strategies In Teaching English Speaking Skill (A Case Study at SMP Negeri 12 Malang) - Ghovinda Ghovinda (Graduate Program, University of Islam Malang, 2022)
The teaching strategies have a significant impact on the students' understanding in a process of learning. This study aimed to investigate the teachers’ strategies and problems faced by the English teachers in applying the strategy especially in teaching English speaking skills at SMP Negeri 12 Malang. The study involved three English teachers as participants of the study. This research design was qualitative research of case study. Based on the end of the result, it was discovered that there were some strategies that the English teachers used in teaching English speaking skills. The strategies that the English teachers used are the active learning method which combines with role-play strategy and the expository learning method which combine it with the drilling strategy. Besides those strategies, the teachers also have another technique to solve any problems in conducted speaking class such as lack of vocabulary, lack of confidence in speaking English and pronunciation problem. To overcome this issue, each of the English teachers has different techniques in solving this problem.